Delivery of bupivacaine from UHMWPE and its implications for managing pain after joint arthroplasty. (15th July 2019) - Grindy, Scott C.; Gil, Dmitry; Suhardi, Jeremy V.; Muratoglu, Orhun K.; Bedair, Hany; Oral, Ebru
Graphical abstract: Abstract: Total joint replacement is a widely used and successful surgical approach. Approximately 7 million US adults are currently living with a hip or knee replacement. However, the surgical procedures for total joint replacement are associated with significant postoperative pain, and current strategies do not adequately address this pain, which leads to patient dissatisfaction, reduced mobility, and increased risk of opioid addiction. We hypothesized that the ultra-high-molecular-weight polyethylene (UHMWPE) bearing surfaces used in total joint prosthetics could provide sustained release of the local anesthetic bupivacaine to provide relief from joint pain for an extended period of time after surgery. In this paper, we describe the production of bupivacaine-loaded UHMWPE (BPE) and measure the in vitro bupivacaine release kinetics of BPE. We found that bupivacaine could be released from BPE at clinically relevant rates for up to several days and that BPE possesses antibacterial effects. Therefore, bupivacaine-loaded UHMWPE is a promising material for joint replacement prostheses, and future studies will evaluate its safety and efficacy in in vivo models. Statement of Significance: Total joint replacement is associated with significant pain and risk of infection. In our paper, we introduce bupivacaine-loaded ultra-high-molecular-weight polyethylene (BPE), which releases bupivacaine, a pain-treating drug, at doses comparable to currently used doses. Additionally, BPE inhibits the growth of infection-causing bacteria. Therefore, BPE may be able to reduce both postsurgical pain and risk of infection, potentially treating two of the most prominent complications associated with total joint replacement. To our knowledge, this is the first development of a material that can address both complications, and devices incorporating BPE would represent a significant advancement in joint arthroplasty prosthetics. More generally, the incorporation of therapeutic agents into ultra-high-molecular-weight polyethylene could impact many orthopedic procedures owing to its ubiquity.